2020
DOI: 10.1002/cam4.3607
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic health is a determining factor for incident colorectal cancer in the obese population: A nationwide population‐based cohort study

Abstract: Background The association of the risk of colorectal cancer (CRC) with obesity or obesity‐induced metabolic disturbances remains controversial. We assessed the association of metabolic health status with incident CRC among subjects with obesity. Methods This study included 319,397 subjects from the Korean National Health Insurance Service‐National Health Screening Cohort. Transitions in metabolic health status and obesity were examined during 2009–2010 and 2011–2012. We categorized subjects with obesity into f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 35 publications
0
20
0
Order By: Relevance
“…Although obesity has been an established risk factor for CRC, it often coexists with other metabolic abnormalities such hyperglycemia, dyslipidemia and hypertension, which may mediate this association between obesity and CRC risk [34][35][36] . Recent studies found that obese individuals without metabolic abnormalities which were referred to "metabolically health obesity (MHO) " had no increased risk of incident CRC whereas those with "metabolically unhealthy obesity (MUO)" showed a higher risk of CRC, raising special concern of MUO [35] . Consistent with these findings, our study included obese individuals with at least one of metabolic abnormalities and did observe a 31% greater risk of CRC.…”
Section: Discussionmentioning
confidence: 99%
“…Although obesity has been an established risk factor for CRC, it often coexists with other metabolic abnormalities such hyperglycemia, dyslipidemia and hypertension, which may mediate this association between obesity and CRC risk [34][35][36] . Recent studies found that obese individuals without metabolic abnormalities which were referred to "metabolically health obesity (MHO) " had no increased risk of incident CRC whereas those with "metabolically unhealthy obesity (MUO)" showed a higher risk of CRC, raising special concern of MUO [35] . Consistent with these findings, our study included obese individuals with at least one of metabolic abnormalities and did observe a 31% greater risk of CRC.…”
Section: Discussionmentioning
confidence: 99%
“…1. Finally, 7 cohort studies [13,[20][21][22][23][24][25], with a total sample size of 759,066 participants met eligibility criteria to be included in this meta-analysis. The studies had been published between 2014 and 2020.…”
Section: Findings From the Systematic Reviewmentioning
confidence: 99%
“…The outcome was colorectal cancer in all studies except for the study by Moore et al [23], which assessed specifically colon cancer. Data for the risk of colorectal cancer for individuals with MUHNW, MHO, and MUHO, compared with subjects with MHNW, were reported in 7 studies with 9 data sets [13,[20][21][22][23][24][25] and 6 studies with 8 data sets [13,20,21,[23][24][25]. The definition of metabolically unhealthy phenotype was according to the presence of metabolic syndrome [13,[20][21][22], and having elevated blood glucose (> 125 mg/dL) [23],…”
Section: Findings From the Systematic Reviewmentioning
confidence: 99%
“…It is recently reported that the increasing bulk of fat in obesity is not the independent contributor to cancer pathogenesis. A cohort study on 319,397 Korean subjects has suggested that the people with obesity derived metabolic derangements are at relatively higher risk of colorectal cancer [ 18 ]. Despite of the high body mass index, the risk of colorectal cancers and cardiovascular ailments was remarkably minimum in a sub-population of obese subjects who did not show metabolic dysregulations such as high blood pressure, hyperinsulinemia, dyslipidemia, and insulin resistance.…”
Section: Introductionmentioning
confidence: 99%